The dynamics of Indonesian language adaptation in virtual communication among Generation Z using acronyms, abbreviations, and code-mixing - Wirahyuni, Kadek; Putrayasa, Ida Bagus; Paramarta, Ketut; Suandi, Nengah; Rasna, Wayan (Indonesian Research Journal in Education |IRJE|, 2025)
The primary objectives of this research were to identify the dominant patterns of acronyms and abbreviations, analyze the linguistic and social factors underlying their usage, and evaluate the impact of this phenomenon on the effectiveness, clarity, and communication norms among Generation Z in Bali. The research employed a sequential explanatory mixed-methods design, involving 450 respondents aged 13-28 years. The research findings indicated a high prevalence of acronyms and abbreviations in Gen Z's communication. The ten most dominant acronyms, such as "baper" (16.1%), "pansos" (12.6%), and "bucin" (11.2%), not only serve an efficiency function but also possess rich pragmatic implications. Similarly, abbreviations like "yg" (18.7%), "udah" (16.3%), and "ga" (15.1%) are frequently used, reflecting a strong preference for typing efficiency. Analysis also revealed that code-mixing occurred in 68.3% of the conversations examined, with lexical insertion (75.2%) being the most dominant type. The primary motivations behind these linguistic adaptations include a strong drive for communicative efficiency (saving typing time), the need to construct identity and foster in-group affiliation, and aspirations towards modernity and globalization.